2018
DOI: 10.1186/s13568-018-0536-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of culture media, pH and temperature on growth and bacteriocin production of bacteriocinogenic lactic acid bacteria

Abstract: There has been continued interest in bacteriocins research from an applied perspective as bacteriocins have potential to be used as natural preservative. Four bacteriocinogenic lactic acid bacteria (LAB) strains of Lactobacillus curvatus (Arla-10), Enterococcus faecium (JFR-1), Lactobacillus paracasei subsp. paracasei (JFR-5) and Streptococcus thermophilus (TSB-8) were previously isolated and identified in our lab. The objective of this study was to determine the optimal growth conditions for both LAB growth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
110
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(141 citation statements)
references
References 37 publications
9
110
0
3
Order By: Relevance
“…; Yang et al . ). At present, a few reports concerning the use of natural or synthetic media for the cultivation of complex natural starters are available in literature (Erkus et al .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…; Yang et al . ). At present, a few reports concerning the use of natural or synthetic media for the cultivation of complex natural starters are available in literature (Erkus et al .…”
Section: Resultsmentioning
confidence: 97%
“…The medium properties can influence bacterial growth, biomass and the production of metabolites (e.g. lactic acid, exopolysaccharides and bacteriocins), thus, stimulating species and strains differently, can change microbial composition and the balance of complex natural starters (Savoie et al 2007;Adebayo-Tayo and Onilude 2010;Marques Saccaro et al 2012;Basu et al 2015;Yang et al 2018). At present, a few reports concerning the use of natural or synthetic media for the cultivation of complex natural starters are available in literature (Erkus et al 2013;Frantzen et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, storage time and temperature can affect the bacterial survival [30,[38][39][40] thus the manipulation of environmental temperature could be useful for reducing the loss of viable bacteria. In general, high temperature importantly decreases microorganism's viability [41,42] while low temperature, like refrigeration, has been reported to be better for the survival of certain probiotics [43].…”
Section: Introductionmentioning
confidence: 99%
“…The pH and lactose were not significant factors to maintain or increase the antifungal capacity of the films. In contrast, it has been reported that the gene expression of antimicrobial metabolites (mainly bacteriocins) is regulated by pH [26]. The pH values evaluated in the present study (4.5 and 5.5) are possibly not high enough to show an effect of pH on genetic regulation; the cited authors evaluated a wide pH range (4.5, 5.5, 6.2, 7.4 and 8.5) and reported that the optimal production of bacteriocins was at pH 6.2.…”
Section: Effect Of Factors On the Antifungal Capacity Of The Tep6 Bacmentioning
confidence: 92%
“…It has been reported that basic pH favors the accumulation of lactate, which can result in the loss of both membrane integrity and metabolic activity. The interaction between the pH and the chemical composition of the culture medium also seems to be important for cell viability, as others reported that survival is higher when LAB are cultivated at basic pH values (7.4 and 8.5) in MRS medium [26]; however, when the same cells were cultured in brain and heart infusion (BHI) broth, pH 5.5 was optimal to maintain cell viability.…”
Section: Cell Viability In Films Stored For 14 Daysmentioning
confidence: 99%